Gen Z Muslimpreneur: Minat Mahasiswa UINSU dalam Membangun Bisnis Halal - Rafly Akbar Tanjung; Raja Ridha Rabbihi; Nurazizah Syahrani (CV. ITTC INDONESIA, 2026)
This study aims to analyze the interest of Generation Z students at the State Islamic University of North Sumatra (UINSU) in developing halal businesses and to identify the factors influencing this interest. This research employs a quantitative descriptive-analytical approach, with data collected through surveys distributed to Generation Z students. The analytical framework is based on the Theory of Planned Behavior contextualized within Islamic entrepreneurship. The findings indicate that students demonstrate relatively high normative interest in halal entrepreneurship, driven by religious awareness and positive perceptions of the halal industry’s growth. However, this interest has not fully translated into entrepreneurial readiness due to limited experience, low entrepreneurial self-efficacy, and perceived structural barriers such as capital access and halal certification procedures. These findings suggest that the development of Gen Z Muslimpreneurs requires not only the internalization of Islamic values but also practical capacity building and supportive entrepreneurial ecosystems within Islamic higher education institutions.